Clinical response and tumor control based on long-term follow-up and patient-reported outcomes in patients with chemodectomas of the skull base and head and neck region treated with highly conformal radiation therapy - Combs, Stephanie; Salehi-Allameh, Bahar; Habermehl, Daniel; Eitz, Kerstin Anne; Welzel, Thomas; Debus, Jürgen (Head & neck, 2014)
The purpose of this study was to evaluate long-term outcome after radiation therapy (RT) for skull base or head-and-neck chemodectomas.
Published online 4 May 2013
Gesehen am 06.10.2020